Penerapan Metode Role Playing Materi Membaca Dongeng Upaya Untuk Meningkatkan Minat Dan Hasil Belajar Siswa - Reza Fiprianti Setiani; Ludfi Arya wardana; Shofia Hattarina (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The success of a class can be supported by making the learning process fun, namely by emphasizing the existence of a learning method. During the learning process the method applied is the Role Playing method where the teaching involves students actively participating in the learning process by acting out scenarios from real life that are relevant to the topic of discussion. The formulation of the problem in this study is, 1) How is the application of the Role Playing Method in Indonesian Language Learning for class III in reading fairy tales in an effort to increase student learning interest at SDN Kedung Caluk? 2) How is the Application of the Role Playing Method in Class III Indonesian Language Learning materials for reading fairy tales in an effort to improve student learning outcomes at SDN Kedung Caluk 2? 3) What are the results of the Application of the Role Playing Method in Class III Indonesian Language Learning materials for reading fairy tales in an effort to increase interest in learning and student learning outcomes at SDN Kedung Caluk 2?. This study uses the method (PTK) by using observation techniques, interviews, tests and documentation. This research took place at SDN Kedungcaluk II with 13 class III student subjects. Data analysis in this thesis uses descriptive data analysis, evaluation, and reflection. The process achieved from implementing the Role Playing method is that it can improve student learning outcomes which initially in the first cycle the learning outcomes only reached 46% but in the second cycle it jumped to 92%.